Evaluation Of The Development Of Social Sciences Educational Study - Adinda Putri Dewanny; Ahmad Djuman Kurniawan; Basar Ihsan; Faisal Alkatsiri; Muhammad Yodhantara (PT. Lancar Media Komunikasi, 2023)
This research aims to evaluate the development of Social Sciences education studies using methods Systematic Literature Review (SLR). This research was carried out by searching and reviewing related library sources and references. Based on this research, it can be concluded that social studies learning in general has not run optimally. Evaluations or improvements need to be carried out by school principals, teachers and the government to support history learning programs that are integrated in social studies. Learning evaluation is very important so that a teacher can find out the extent of students' progress. Because knowledge about student progress also has various uses and improvements to the learning system. As we know, learning is a system that has various components such as objectives, materials, methods, media and learning resources, environment, teachers and students. Social studies learning itself is expected to be able to make a good impression in the hearts of students. So that it makes students social creatures who can socialize or interact well in society. More than that, students are expected to be able to become individuals who know their environment, know that the world is wide, know the diversity in the world, know how to interact well in society, and how they will be useful in society in the future. It also allows students to access material easily, anywhere and at any time, not just limited to material presented by teachers when studying at school. Keywords: Development Evaluation, Learning, Social Sciences education